New Polymeric Ion Selective Electrode for Determination of Sulfamethoxazole in Pure and Pharmaceutical Samples. - Abrahem, Sarra A; Al-Saidi, Khaleda H (Al-Nahrain Journal of Science, 2018)
Sulfamethoxazole ion selective electrodes were constructed based on sulfamethoxazole - tengestophosphoric acid as ion pair complex in a polyvinylchloride matrix and plasticized by four plasticizers, Di-octyl phthalate (DOPH); Tri-butyl phosphate (TBP); Acetophenone (AP) and Nitrobenzene (NB). Sulfamethoxazole electrodes (E1, E2, E3 and E4) gave slopes (52.008, 58.381, 56.909 and 50.309 mV/decade) and linear ranges from (1×10-5-1×10-2,1×10-7-1×10-2,1×10-5-1×10-2 and 1×10-5-1×10-2 M) respectively. The best electrode (E2) was based on TBP plasticizer which gave a slope 58.381mV/decade, correlation coefficient 0.9997, detection limit of 9×10-8 M, lifetime 27 day. pH and life time of the electrodes were also studied and the proposed electrode displayed a good stability and reproducibility and were used to determine the Sulfamethoxazole in pharmaceutical samples. The interferences measurements in the presence of (Na+, K+, Cu+2, Mn+2, Fe+3, Al+3, trimethoprim, starch, sucrose and gelatin) were studied using the separated method and mixed method for selectivity coefficient determination.